In(xy) = e^(x+y)
(xy)'/xy = (x+y)' e^(x+y)
(x'y + xy')/xy = (1+y') e^(x+y)
(y + xy')/xy = (1+y')e^(x+y) and simplify
Hope this helps
Positive 3, If You're starting at -6 and you add the first 6 it's at 0, now you have 3 more to add to make 9. And that gives you positive 3. or if you do 9 - 6 you can get your answer that way too.
The answer is 1.144. You can find the answer key in Khan acadmy or even on quizlet
Step-by-step explanation:
f(x) = 6x - 4
f(8) = 6(8) - 4
= 48 - 4
= 44
Is there a picture to go with this ?